Pyogenic granuloma in a 6-year-old boy - a rare case report - Gera, Divya; Anshul Tanwar; Anant G. Nigam; Shradha Jain; Vipul Sharma (International Journal of Contemporary Pediatrics, 2023)
The gingiva, also known as the gums, is the pink-coloured keratinized mucosa that surrounds and protects the teeth. Gingival enlargement or gingival overgrowth, a common trait of gingival disease, is characterized by an increase in the size of gingiva. Irritation fibroma is an exophytic soft tissue mass in the oral mucosa. Indeed, it is not a real neoplasm, but a focal hyperplasia of fibrous connective tissue induced by local trauma or chronic irritation. Pyogenic granuloma is one of the inflammatory hyperplasia seen in the oral cavity, majority are found on the marginal gingiva with only 15% of the tumours on the alveolar part. It predominantly occurs in the second decade of life in young females, male to female ratio is 1:99, and size of lesion varies in diameter from few millimetres to several centimetres. This article presents a case of pyogenic granuloma in an 6year old boy who presented with a gingival overgrowth in his mandibular left buccal surface region i.r.t 31 including marginal and attached gingiva. He had discomfort during mastication, interferes with occlusion there was episode of bleeding during brushing. The lesion was excised and histopathological report confirmed the diagnosis. Case was followed up for six months and no recurrence of the lesion. Etiological factors, clinical features, differential diagnosis and different treatment options are discussed based on the review of current literature available.